New occurrence of the rare genus Doliocatella (Stigonematales, Cyanophyceae) - Branco, LHZ; Necchi, O. (Gebruder Borntraeger, 1999)
A new occurrence of the genus Doliocatella (Cyanophyceae, Cyanobacteria) is reported. The type species of the genus, D. formosa, is described from a stream of the tropical Amazonian rainforest (Manaus, Amazonas State, Brazil). A detailed taxonomic description with photomicrographs and ecological characteristics are provided based on the three worldwide species records. D. formosa is characterized by the presence of uniseriate main filaments, cylindrical branches, and mostly cylindrical cells; heterocytes are absent. D. formosa occurs under limited and special conditions, i.e. habitats with low pH and relatively high temperatures. The species has a restricted ecological distribution, limited to tropical lotic ecosystems, but it is found over a relatively wide geographical range.